DNA ambiental de sedimentos de ecossistemas costeiros em Valença, Bahia, com foco em genes de resistência bacteriana - Santos, Itana Almeida dos (2023)
Environmental surveillance through environmental RNA and DNA is an important strategy for pathogen monitoring in urban surroundings, especially regarding detection of genes of resistance to antibiotic (ARGs). Additionally, the quality of ecosystems can be verified through study of microbial diversity. From the perspective of One Health, which considers that human, animal and environmental health are complementary, it is possible to develop strategies and technologies exchange between different public and private sectors to investigate and mitigate environmental and public health problems. Pollution is one of the most concerning environmental problems, and it reflects on contamination of soil, air and water. The massive liberation of antimicrobial drugs used on animal and human health on ecosystems contribute to ARG selection. The objective of this dissertation is to investigate, in an integrated way, Public Health and Environmental Conservation questions, through analysis of composition of microbial communities in sediments of water. For this, environmental DNA of four estuary regions in different status of conservation in Valença, Bahia, Brazil, was investigated. TetA, tetB, tetE, qnrA, qnrB, catA, blaSHV, blaTEM and sulI genes was quantified through qPCR and additionally, was performed metagenomics of 16S rRNA amplicon for the study of microbial community composition in each sample point. In Guaibim-1, a residential area, there was greater diversity of ARGs, followed by samples collected on Una. Both of them have exclusive genes. This study detected microorganisms generally associated with multiresistance to antibiotics (Enterococcus faecium, Acinetobacter sp, Klebsiella pneumoniae e Enterobacter cloacae), in addition to other microorganisms associated with serious infections. In Guaibim-1 and Taquari, resistance genes were also detected, but in less quantity and no organisms associated to multiresistance were found. The bacterial phyla more abundant was Proteobacteria, Bacteroidetes, Actinobacteria, Chloroflexi and Firmicutes, but the relative abundance of these phyla varied according to the samples. The results imply that Guaibim-2 and Una are more impacted by human effluents and Guaibim and Taquari are more conserved.